Fabrication And Characterisation Of Magnetorheological Elastomers Based On Natural Rubber, Carbonyl Iron And Waste Natural Rubber Glove Powder - Lai, Ngoc Thien (2019)
Magnetorheological elastomers (MREs) are a new class of elastomeric composites consisting of a rubber matrix and magnetic particles. In this work MREs based on natural rubber (NR), waste natural rubber glove powder (WGP) and carbonyl iron particles (CIP) were successfully produced. The Taguchi method was utilised to study the effect of three pre-structuring factors - time, temperature and applied magnetic field on tan δ and tensile properties and predict the optimum combination of factors. Results indicated that magnetic field had the greatest influence on tan δ over 1 – 100 Hz frequency range while pre-curing time and magnetic field had the greatest influence on tan δ over 0.1 – 6% strain amplitude range. However, none of the factors exhibited significant influence on tensile properties. The optimum pre-structuring conditions were then applied to fabricate MREs with the addition of WGP in attempt to enhance damping. Dynamic mechanical analysis showed that addition of WGP improved dynamic performance of MREs. The highest tan δ was obtained with 10 phr WGP, with an increment of 10% in frequency sweep test and a 30% increment in amplitude sweep test. However, obvious gaps and particle pull-out were evidenced by SEM, suggesting weak interfacial bonding between CIP and WGP with the rubber matrix. Consequentially, bis-(3-triethoxysilylpropyl) tetrasulphane (TESPT) was used to improve the interfacial adhesion between rubber and CIP. Coupling occurring between rubber and CIP was identified by FTIR spectra, crosslink density by swelling test and the grafting percentage by thermogravimetric analysis. The optimum content of TESPT was found at 4 phr, with an average increment in tan δ of 40% over a 1 – 100 Hz frequency range and 13% over a 0.1 – 6% strain amplitude.